ASSESSMENT OF FUNCTIONAL CAPACITY IN DIABETIC ELDERLY PEOPLE IN THE COMMUNITY (CIPEEX, 2025)
The assessment of functional capacity in elderly individuals is a relevant parameter for clinical interventions, in addition to the early detection of vital decline in this population. The present study aimed to assess the functional capacity of elderly people with diabetes in the community. Sociodemographic and economic data, presence of diabetes, and functional capacity (Six-Minute Walk Test) were collected at the Reference Center for Hypertension and Diabetes (CRHD) in Rio Verde, Goiás. Individuals aged 60 years or older, without motor, neurological, or cognitive deficits participated. Among the 110 elderly individuals interviewed, the majority were female (75.5%; n=83), Caucasian (55.5%; n=61), without a partner (59.1%; n=65), had an average of 7.7 years of education, and had a functional capacity level of 1 (n=83). n=83), Caucasian (55.5%; n=61), without a partner (59.1%; n=65), had an average of 7.7 years of schooling, a monthly income of 2.2 minimum wages, and negative self-perceived health (91.8%, n=101). The prevalence of diabetes was 51.8% (n=57), and a significant difference in functional capacity was observed between the groups with and without diabetes (p=0.018). These findings showed that more pronounced limitations in activities of daily living and mobility in this population highlight the relevance of public policies aimed at preserving functionality and promoting healthy and active aging.
Keywords: Elderly health; Aging; Diabetes mellitus; Functional capacity